2006
DOI: 10.1002/ar.a.20283
|View full text |Cite
|
Sign up to set email alerts
|

Whisker maps in marsupials: Nerve lesions and critical periods

Abstract: In the wallaby, whisker-related patterns develop over a protracted period of postnatal maturation in the pouch. Afferents arrive simultaneously in the thalamus and cortex from postnatal day (P) 15. Whiskerrelated patterns are first seen in the thalamus at P50 and are well formed by P73, before cortical patterns first appear (P75) or are well developed (P85). This study used the slow developmental sequence and accessibility of the pouch young to investigate the effect of nerve lesions before afferent arrival, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The layout of the opossum mystacial pad is quite similar to that of the wallaby (Waite et al, 2006) as there seem to be four rows of vibrissae in both species, with two nasal whiskers present in the dorsal-most row. Weller (Weller, 1993) also found two dorsal-most whiskers in brush-tailed opossums; however, that study reported six rows of whiskers in total (or five if their row A is labelled as nasal whiskers).…”
Section: Organisation Of the Facial Vibrissaementioning
confidence: 86%
“…The layout of the opossum mystacial pad is quite similar to that of the wallaby (Waite et al, 2006) as there seem to be four rows of vibrissae in both species, with two nasal whiskers present in the dorsal-most row. Weller (Weller, 1993) also found two dorsal-most whiskers in brush-tailed opossums; however, that study reported six rows of whiskers in total (or five if their row A is labelled as nasal whiskers).…”
Section: Organisation Of the Facial Vibrissaementioning
confidence: 86%
“…In the wallaby there is a clear increase in the non‐NMDA to NMDA ratio during development, suggesting that there are no major differences in the pattern of maturation of glutamatergic synaptic transmission between the species. There may, however, be differences in the relative timings of these events which may in turn correlate with the observation that the critical period for pattern formation in the cortex (as visualized using mitochondrial enzymes which can reflect organization of pre and/or postsynaptic strucutures) terminates during the period that patterns form in the wallaby (Waite et al ., 2006) but in mice has been reported to extend beyond it to P5 (Woolsey et al ., 1979). It would also be of interest to determine whether there are differences in the downstream signalling pathways which mediate developmental plasticity in the somatosensory cortex of mice and wallabies.…”
Section: Discussionmentioning
confidence: 93%
“…It is tempting to speculate that the appearance of the fast, non‐NMDA‐dominated component, which we suggest may be required to produce firing of postsynaptic neurons, is necessary to drive pattern formation. The time at which the non‐NMDA‐mediated component becomes dominant also correlates with the end of the critical period for pattern formation in the somatosensory thalamus and cortex of the wallaby as visualized with cytochrome oxidase (Waite et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2b). These structures have been detected in some rodents (mice, rat, hamster Cricetus cricetus; Woolsey et al 1975), marsupials (wallaby Macropus eugenii; Woolsey et al 1975, Waite et al 2006, pinnipeds (California sea lion Zalophus californianus; Sawyer et al 2016), and nocturnal primates (northern greater galago Otolemur garnettii; Sawyer et al 2015), but are absent in the guinea pig Cavia porcellus and beaver Castor fiber (Woolsey et al 1975), and many species have not yet been investigated. This one-to-one mapping of whisker signals ascending through the brain to somatosensory cortex has inspired many neuroscientists to use this system as a model of mammalian sensory processing, since signals can be traced from the whisker to the cortex.…”
Section: How Do Whiskers Work?mentioning
confidence: 99%